2021
DOI: 10.1126/scisignal.abk0599
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo signaling pathway effector YAP promotes salivary gland regeneration after injury

Abstract: YAP stimulates the proliferation and regenerative potential of ductal cells after salivary gland injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Following the collection of submandibular salivary glands, tissue isolation was performed as previously described 56 . In summary, after mechanic and enzymatic digestion, cells were cultured in DMEM/F12 complemented with penicillin-streptomycin (Pen/Strep) antibiotics, glutamax (2 mM), EGF (20 ng/ml); FGF2 (20 ng/ml), N2 (1x), insulin (10 µg/ml) and dexamethasone (1 uM).…”
Section: Organoid Culture and Self-renewal Assaymentioning
confidence: 99%
“…Following the collection of submandibular salivary glands, tissue isolation was performed as previously described 56 . In summary, after mechanic and enzymatic digestion, cells were cultured in DMEM/F12 complemented with penicillin-streptomycin (Pen/Strep) antibiotics, glutamax (2 mM), EGF (20 ng/ml); FGF2 (20 ng/ml), N2 (1x), insulin (10 µg/ml) and dexamethasone (1 uM).…”
Section: Organoid Culture and Self-renewal Assaymentioning
confidence: 99%
“…The deletion of the YAP gene in mice resulted in a lack of epithelial patterning in the developing gland [ 48 ]. Rocchi et al reported that YAP overexpression resulted in the stem/progenitor cell mediated SG organoid expansion in three-dimensional cultures [ 49 ]. They also reported that translocation of YAP to the nucleus can induce activation of new ductal cells, which can be utilized for SG regeneration after severe radiation injuries [ 49 ].…”
Section: Tuning Ideal Hydrogel Properties For Sg Tissue Engineeringmentioning
confidence: 99%
“…Rocchi et al reported that YAP overexpression resulted in the stem/progenitor cell mediated SG organoid expansion in three-dimensional cultures [ 49 ]. They also reported that translocation of YAP to the nucleus can induce activation of new ductal cells, which can be utilized for SG regeneration after severe radiation injuries [ 49 ]. It is noted by other researchers that this cytoplasm-to-nuclear translocation of YAP occurs in response to an increment in the ECM stiffness, leading to the proliferation of different cell types such as fibroblasts [ 50 ].…”
Section: Tuning Ideal Hydrogel Properties For Sg Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…35−37 Furthermore, efforts have been directed toward comprehending how ECM remodelling and the physicochemical properties of biomaterials influence the SG phenotype and secretory functions, which are paramount for successful clinical applications. 34,38,39 Clinical trials, on the other hand, have centered on delivering stem cells and their derivatives from different sources to alleviate xerostomia. In recent times, a handful of human clinical trials have demonstrated the promising potential of autologous mesenchymal stem cells (MSCs) in the treatment of radiation-injured salivary glands.…”
Section: ■ Introductionmentioning
confidence: 99%